Reliability Analysis of Fire Stairs in Hospital Buildings (Case Study: Malahayati Islamic Hospital and University of North Sumatra Hospital) - Zielisa Nur Qadimah; N. Vinky Rahman (International Journal of Architecture and Urbanism, 2019)
One important aspect of hospital buildings is the safety of the occurrence of fire hazards, especially in the fire stairs. The hospital is classified as very crowded because of the large number of inpatients or outpatients who consult at the Malahayati Islamic Hospital or the University of North Sumatra Hospital, both middle and upper-middle class. Because the density level of occupants in hospital buildings is high, it requires a fire ladder that meets the standards, how to apply the fire ladder reliability system and its future recommendations on the Malahayati Islamic Hospital building and the University of North Sumatra Hospital. This study aims to determine the application and analyze the level of reliability of fire stairs in hospital buildings. This study uses data analysis method, namely AHP (Analytical Hierarchy Process) which is based on very effective research to help solve problems in the fire stairs reliability system in the case study of the Islamic Hospital Malahayati, the level of reliability is sufficient, while the University of North Sumatra Hospital has a very good level of reliability. Several design recommendations were made and tested to increase the reliability of fire stairs at Malahayati Islamic Hospital and the University of North Sumatra Hospital; the results can be improved.